Optimising stator vane settings in multistage axial flow compressors - White, Nicholas M. (Cranfield University, 2002)
There is a common requirement in the process, oil and gas turbine industries for high performance axial flow compressors operating over a wide range of mass flow rate and rotational speed at high efficiency. The trends have been for higher blade loadings (greater pressure rise per stage) and higher efficiency which are increasingly achieved through sophisticated Computational Fluid Dynamics designs. These trends, however, tend to mitigate against stable operating flow range (reduced surge margin), which can often lead to performance compromises. The objective of this work is to investigate the possibility of using alternative means to gain ow range by better use of variable geometry, which may permit design objectives to be better achieved. Variable geometry of the type envisaged is already often employed to overcome part-speed operating problems, but it proposed here that there may be additional benefits from their more intelligent control. The operation of axial compressors with a wide operating range is limited by instabilities, which cause a full breakdown of the flow, which is surge. These instabilities, which are caused by high incidence and subsequent stalling of stages occur due to different phenomena at part and full speed operation. The problem at part-speed is that the front stages are often heavily stalled and rear stages choked, whereas at high speeds, the front stages are operating close to choke and the rear stages tend to be stalling. Optimisation of the design to full load conditions can often provide part-speed problems and to achieve the acceptable performance, variable geometry over the front region of the compressor is sometimes used to modify the flow angles and avoid stage stall and subsequent surge. To-date, such variable settings follow some schedule established by analysis and experiment whereas this work presents a methodology of setting blade rows using an optimisation procedure and investigates the likelihood of performance benefits being obtained by a control technique which reacts° to these changing conditions. The construction of the numerical method presented in this thesis was done with an emphasis upon its intended contribution towards a eventual online control application. Therefore, a practical approach has been employed in the development of the compressor modelling techniques used in the work. Specifically, a highly empirical one-dimensional performance prediction code was constructed, employing successful correlations taken from the literature. This was coupled to a surge prediction method that has been shown in the past to function more than satisfactorily in a multistage environment. Finally, the predicted stage and overall performance (including the surge point) characteristics were passed to a optimisation program, which allowed these simulated conditions to be investigated. It is hoped that the work presented has illustrated the potential (from a aerodynamic performance point of view) of such a control technique to offer additional freedom in the operation of a multistage axial flow compressor. Moreover, the numerical modelling techniques have been developed enough to envisage (at least in part) their simple integration within a practical system. Clearly, some further investigations are required to take this work forward and the next logical step would be to improve the empirical rules with which the blade performance is predicted. A experimental programme would also be of great advantage, for example in the study of how the deviation angle for a given blade row varies over time (operating hours) in a real machine due to ageing and fouling. This would allow better estimates of the stage work during long term operation so that the optimiser could adapt to the slowly degrading performance of the blades. Finally, it is important to verify the simulated results with measured data, taken at the same optimal stator vane settings as given by the program. This must be carried out before it can be applied to a real application, although a limited study of this nature is presented in chapter 6.